The Relationship of Gender Role Attitude and Division of Household labor with Couples' Perceived justice - Shahla Nourani; Fatemeh Seraj shirvan; Mohammad Taghi Shakeri; Naghmeh Mokhber (Mashhad University of Medical Sciences, 2019)
Background & aim: Given the advancements in science, technology, and cultural globalization, Iranian families has changed in several aspects affecting individual's perception of justice in division of household labor. Therefore, we sought to evaluate the correlation of gender role attitude and household labor division with perceived justice in couples. Methods: The present correlational study was conducted in 180 couples visiting healthcare centers of Mashhad, Iran, in 2014. The participants were selected through the three-stage cluster sampling method. Data collection tools included questionnaires of gender role attitude, participation in household labor, and perceived justice. Spearman rho and Pearson correlation coefficient were run in SPSS, version 16. Results: A significant correlation was seen between women's gender role attitude with their involvement in household labor and perceived justice (P=0.04, P=0.03, respectively). But there was no correlation between their involvement in household labor and perceived justice (P=0.83). There was no correlation between men's gender role attitude and their involvement in household labor (P=0.61), whereas their gender role attitude was correlated with perception of justice (P=0.01, r=-0.13). There was also a direct correlation between male involvement in household labor and perceived justice (P=0.00, r=0.19). Conclusion: Most employed women despite having modern gender role attitudes, had still more involvement in household labor. Almost half of men who had traditional gender role attitudes, reported appropriate involvement in household labor. Men with more involvement in household labor had a higher perception of justice.